2010
DOI: 10.3758/s13421-010-0016-5
|View full text |Cite
|
Sign up to set email alerts
|

Between- and within-language priming is the same: Evidence for shared bilingual syntactic representations

Abstract: Two structural-priming experiments investigated how bilinguals represent syntactic structures. According to the shared-syntax account (Hartsuiker, Pickering, & Veltkamp, 2004), bilinguals have a single syntactic representation for structures that exist in both languages, whereas separatesyntax accounts claim that the representations for these structures are language specific. Our experiments tested native speakers of Swedish who were highly proficient in English. The results showed that structural priming with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
128
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(142 citation statements)
references
References 56 publications
12
128
2
Order By: Relevance
“…In these conditions, within-language priming was descriptively slightly larger than between-language priming, but this difference was not statistically significant. Note that a recent reanalysis of these data (reported inHartsuiker & Bernolet, in press) showed that the difference between withinlanguage and between-language depended on L2 proficiency, with a smaller difference for more proficient subjects.Similarly, Kantola and Van Gompel (2011) reported two structural priming experiments using datives from L2 English and L1 Swedish to Swedish and English. They tested highly proficient subjects (master's students of English) and used a written sentence completion paradigm (Pickering & Branigan, 1998).…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…In these conditions, within-language priming was descriptively slightly larger than between-language priming, but this difference was not statistically significant. Note that a recent reanalysis of these data (reported inHartsuiker & Bernolet, in press) showed that the difference between withinlanguage and between-language depended on L2 proficiency, with a smaller difference for more proficient subjects.Similarly, Kantola and Van Gompel (2011) reported two structural priming experiments using datives from L2 English and L1 Swedish to Swedish and English. They tested highly proficient subjects (master's students of English) and used a written sentence completion paradigm (Pickering & Branigan, 1998).…”
mentioning
confidence: 98%
“…Similarly, Kantola and Van Gompel (2011) reported two structural priming experiments using datives from L2 English and L1 Swedish to Swedish and English. They tested highly proficient subjects (master's students of English) and used a written sentence completion paradigm (Pickering & Branigan, 1998).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…then, many others have evaluated the workings of structural persistence in all of these areas, expanding knowledge about the impact of structural persistence within and across an array of different languages (e.g., Cai et al 2011;Desmet and Declercq 2006;Pérez-Leroux et al 2009;Hartsuiker et al 2004;Salamoura and Williams 2007;Shin and Christianson 2009), about its manifestations in transfer (e.g., Hatzidaki et al 2011;Pyers and Emmorey 2008) and codeswitching (e.g., Kootstra et al 2012), about the representation of syntax in bilinguals (e.g., Bernolet et al 2007;Hartsuiker and Pickering 2008;Kantola and van Gompel 2011;Schoonbaert et al 2007), and about crosslinguistic similarities and differences in language structure (e.g., Arai 2012).…”
mentioning
confidence: 99%